2013
DOI: 10.1159/000350028
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Time to Discharge in Patients Hospitalized for Behavioral and Psychological Symptoms of Dementia

Abstract: Background/Aims: In Japan, more than 50,000 patients with dementia are housed in psychiatric facilities, a trend precipitated by prolonged hospitalizations. This study aimed to determine predictors for the time to discharge in patients hospitalized for behavioral and psychological symptoms of dementia (BPSD). Methods: Medical charts of patients admitted to an acute psychogeriatric ward for treatment of BPSD were reviewed. Cox's proportional hazards model was used to evaluate relationships between active behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Overactivity included non‐aggressive behaviour that required monitoring, such as aimless wandering, trying to reach a different place, restlessness, or repetitive actions and/or mannerisms. Apathy/depression included serious apathetic or depressive behaviour, such as severe loss of appetite, refusal to eat, refusal to take medication, or suicidal tendencies …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overactivity included non‐aggressive behaviour that required monitoring, such as aimless wandering, trying to reach a different place, restlessness, or repetitive actions and/or mannerisms. Apathy/depression included serious apathetic or depressive behaviour, such as severe loss of appetite, refusal to eat, refusal to take medication, or suicidal tendencies …”
Section: Methodsmentioning
confidence: 99%
“…13 Previously, we demonstrated that patients' clinical and environmental characteristics at the time of admission are closely associated with time to discharge. 14 In the present study, we examined the frequency of HD in relation to patient profiles at the time of admission and determined factors that could be used to predict HD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the effectiveness of treatment of BPSD at hospital (Bellelli et al, 1998; Colombo et al, 2007; Kitamura, Kitamura, Hino, & Kurata, 2013; Rouch et al, 2017; Sugiyama et al, 2013; Taniguchi et al, 2013). However, there are some issues associated with the treatment in hospital.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the prolonged hospitalization is one of the issues in Japan. Many patients still stayed at hospital even after improvement of BPSD (Kitamura et al, 2013; Taniguchi et al, 2013). Various factors have been identified as the predictors of the prolonged hospitalization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation